Modeling the grain growth kinetics of doped nearly fully dense nanocrystalline ceramics. Issue 9 (15th June 2017) - Gong, M.M.; Chang, C.H.; Wu, L.J.; Dey, S.; Castro, R.H.R.; Liu, F.
Abstract: A grain growth model to describe dopant effects on nanocrystalline ceramics is proposed by incorporating the dopant-segregation-dependent grain boundary (GB) energy and the GB mobility subjected to intrinsic drag and pore drag (both affected by dopant segregation) into the parabolic growth formula. The model addresses the common case of residual porosity in grain growth behavior. Taking near-fully dense nanocrystalline lanthanum doped Yttria stabilized Zirconia (La doped YSZ) as the system of study, the grain growth behavior was explored using the model. The substantially suppressed grain growth in La doped YSZ as compared to La-free YSZ could be attributed to the combined effect of thermodynamically reduced GB energy and kinetically reduced GB mobility. Contrary to previous assumptions, the model suggests that, relative to the GB energy overall effect, the effect of the dopant on the GB mobility plays a more significant role in reducing coarsening. Furthermore, model calculation shows that both intrinsic drag and pore drag makes certain contribution to the evolution of GB mobility during the grain growth.